Virological characteristics of SARS-CoV-2 Omicron BA.5.2.48 - Wang, Wenqi; Jin, Qiushi; Liu, Ruixue; Zeng, Wentao; Zhu, Pengfei; Li, Tingting; Wang, Tiecheng; Xiang, Haiyang; Zhang, Hang; Chen, Qin; Gao, Yun; Lai, Yana; et al. (Frontiers in Immunology, 2024)
With the prevalence of sequentially-emerged sublineages including BA.1, BA.2 and BA.5, SARS-CoV-2 Omicron infection has transformed into a regional epidemic disease. As a sublineage of BA.5, the BA.5.2.48 outbroke and evolved into multi-subvariants in China without clearly established virological characteristics. Here, we evaluated the virological characteristics of two isolates of the prevalent BA.5.2.48 subvariant, DY.2 and DY.1.1 (a subvariant of DY.1). Compared to the normal BA.5 spike, the double-mutated DY.1.1 spike demonstrates efficient cleavage, reduced fusogenicity and higher hACE2 binding affinity. BA.5.2.48 demonstrated enhanced airborne transmission capacity than BA.2 in hamsters. The pathogenicity of BA.5.2.48 is greater than BA.2, as revealed in Omicron-lethal H11-K18-hACE2 rodents. In both naïve and convalescent hamsters, DY.1.1 shows stronger fitness than DY.2 in hamster turbinates. Thus regional outbreaking of BA.5.2.48 promotes the multidirectional evolution of its subvariants, gaining either enhanced pathogenicity or a fitness in upper airways which is associated with higher transmission.